The non-English major lecturers speak English: The barriers encountered by adult learners - Madkur, Ahmad (Journal on English as a Foreign Language (JEFL), 2018)
This study was aimed at investigating the difficulties and problems faced by non-English major lecturers when they were taking a part in English discussion. This study was a qualitative descriptive research involving 10 non-English major lecturers who took a part in a twice-a-week discussion so-called English Corner. To collect the data, in-depth interview and observation were used. The collected data were analyzed by using Miles and Hubermanâs interactive data analysis data model consisting of data reduction, data display and data verifying. The result of the study showed that those barriers could be classified into three problems namely socio-cultural, linguistic and interpersonal problems. The found barriers were expected to be a consideration to find out the solution to make the betterment of English learning among lecturers with the non-English background of study.